Descriptions of six new species of Midoria (Hemiptera: Cicadellidae: Ledrinae) from China with a key to the species of the genus - Li, Yu-Jian; Li, Zi-Zhong (Zootaxa, 2011)
The paper deals with six new species of the genus Midoria Kato, 1931 (Hemiptera: Cicadellidae: Ledrinae), Midoria denticulata sp. nov., Midoria deplanata sp. nov., Midoria zunyiensis sp. nov., Midoria hamulata sp. nov., Midoria torsiva sp. nov. and Midoria hastifera sp. nov.. A key to distinguish all species of the genus (except Midoria capitata Kato) is given. The type specimens of new species are deposited in the Institute of Entomology, Guizhou University (GUGC).